Factors affecting the performance of flood control, drainage and irrigation projects in Bangladesh: a case study - Miah, Md. Mirjahan; Mohit, Mohammad Abdul (The Institution of Engineers Bangladesh, 1998)
This paper presents the results of a study carried out to evaluate the performance of Karnafuli Irrigation Project. The data were collected through review of project documents, field inspection, inetrview with service providers and beneficiaries. The achievement of the project for irrigation was found to be quite satisfactory but the flood control and drainage benefits could not be realized as expected. This is partly because of some deficiencies in planning, design and implementation of the project. Major operation and maintenance problems include inadequate fund, shortage of manpower at the field level and lack of beneficiaries participation. The agricultural development constraints are: adverse land tenure, lack of agricultural credit and poor extension services. The performance of the project may be improved through effective participation of beneficiaries in operation and maintenance.